A holistic approach toward development of plant-based meat alternatives through incorporation of novel microalgae-based ingredients - Bakhsh, Allah; Park, Juhee; Baritugo, Kei Anne; Kim, Bosung; Sil Moon, Sung; Rahman, Attaur; Park, Sungkwon (Frontiers in Nutrition, 2023)
This study explored the changes in the physiochemical, textural, sensory, and functional characteristics of plant-based meat (PBM) after incorporating novel plant-based ingredients including spirulina (SPI), duck Weed (DW), and yellow Chlorella (YC). In the chromaticity evaluation, the YC group (YCI% YC2% and YC3%) displayed significant differences (p < 0.05) in lightness (L*) indices as compared to the control. Whereas, based on concertation gradient of SPI microalgae (SP0.5%, SP0.7%, and SP1%) incorporated into PBM patties demonstrated that SPI 1 had the lowest values (p < 0.05) in redness (a*) and yellowness (b*) followed by SPI 0.7 and SPI 0.5% concentration respectively. The concentration gradient of the YC group indicated that YC3 was intended to be the highest crude fat value followed by YC2 and YCI. The ash content in PBM patties increased considerably (p < 0.05) as the concentration level of microalgae advanced in all treated groups. Based on the concentration level of YC incorporated microalgae into PBM patties indicated that YC 3 had the highest (p < 0.05) gumminess and chewiness while YC 1 had the lowest reported values in terms of gumminess and chewiness. Moreover, springiness and cohesiveness showed considerable differences between SPI and YC groups. In the sensory evaluation, SPI 1 showed the lowest value only in color and appearance (p < 0.05), conversely, the other sensory parameters were non-significant among all treatment groups (p > 0.05). The micronutrient in PBM presented an irregular pattern after incorporating various ingredients. However, levels were higher (p < 0.05) in the DW group (DW 0.5% DW 0.7%, and DW% 1) than those in the other groups. Moreover, the SPI and YC groups showed detectable levels of DPPH radical scavenging activity with, SP 1 showing the highest level of antioxidant activity. Acknowledging the limited research on PBM production, extraction technologies, and selecting various novel suitable ingredients in meat substitutes. To the best of our knowledge, this is the first report that describes the physiochemical, textural, sensory, and nutritional attributes of PBM incorporated with novel microalgae.